Ultrasonography assessment of hepatobiliary abnormalities in 3,359 subjects with Opisthorchis viverrini infection in endemic areas of Thailand - Mairiang, Eimorn (2011)
A cross sectional study on hepatobiliary abnormalities in opisthorchiasis was performed in 8,936 males and females aged from 20 to 60 years from 90 villages of Khon Kaen province, Northeast Thailand. All were stool-examined for Opisthorchis viverrini infection by standard quantitative formalin/ethyl acetate concentration technique. Of these, 3,359 participants with stool egg positive were underwent ultrasonography of the upper abdomen. The hepatobiliary abnormalities detected by ultrasound are described here. This study found a significantly higher frequency of advanced periductal fibrosis in persons with chronic opisthorchiasis (23.6%), particularly in males. Risks of the fibrosis included intensity of infection, and age younger than 30 years. Height of left lobe of the liver, cross-section of the gallbladder dimensions post fatty meal, sludge, and, interestingly, intrahepatic duct stones were significantly associated with the advanced periductal fibrosis. Eleven suspected cholangiocarcinoma (CCA) cases were observed. This study emphasizes the current status of high O. viverrini infection rate and the existence of hepatobiliary abnormalities including suspected CCA in opisthorchiasis endemic areas of Thailand.